2016
DOI: 10.1089/jayao.2016.0015
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Posttraumatic Stress Symptoms in Adolescents and Young Adults with Cancer and Their Parents

Abstract: Despite numerous studies of AYA cancer survivors, very few studies have examined the psychosocial and psychological impacts of cancer when onset occurs during adolescence and young adulthood. Almost no studies have examined the impacts on their parent caregivers. The findings of this study support the need for early identification of psychological distress, appropriate developmental perspectives to understand AYA distress, and the need for family-based psychological assessment and interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 27 publications
4
75
0
Order By: Relevance
“…23 In a sample of Australian AYA’s, almost half were classified as being above the cutoff score for PTSS. 24 FOR is also common in young adult cancer survivors. Just over half of young adult breast cancer survivors in one study reported moderate to high levels of FOR.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In a sample of Australian AYA’s, almost half were classified as being above the cutoff score for PTSS. 24 FOR is also common in young adult cancer survivors. Just over half of young adult breast cancer survivors in one study reported moderate to high levels of FOR.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
“…This was found in the National Longitudinal Study of Adolescent Health 30 and the Australian cohort study described above. 24 The Australian study identified additional risk factors for elevated distress, which included lower social support, low self-image, and identity issues. More intensive treatment also is predictive of more distress.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
“…However, our response rate is similar to other studies examining AYA experiences of care or QOL (25% and 31%). A recent Australian study recruiting AYAs through hospitals also achieved a response rate under 30% (26%). However, recruitment through CRs ensured that the sample was not biased towards patients attending specific treatment centres or AYA clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Given that family support can buffer distress, the healthcare team should work to support family functioning and relationships. Parents who are geographically isolated, have other life stressors, lack social support of their own, and whose child has relapsed appear particularly at risk of depression, anxiety, and posttraumatic stress symptoms …”
Section: Principles Of Aya Cancer Carementioning
confidence: 99%